Family satisfaction in intensive care units: integrative literature review - Mar, Maria João (2020)
Background: due to the difficulty of evaluating and intensive care unit (ICU) patient’s satisfaction, family satisfaction must be taken into consideration when assessing the quality of the care provided in these units. Objectives: evaluate the feasibility of the quiz 'FS-ICU-24'as an instrument to assess family satisfaction; identify satisfaction levels through a questionnaire with an emphasis on items where satisfaction levels are lower and strategies to increase it. Methodology: an integrative review that analyzes relevant articles published in EBSCO and in FSICU.org data bases between 2014 and 2019. Key words: patient satisfaction; critical care; FS-ICU-24. In order to achieve systematized information, a table with the following points was prepared: authors and publication date, country, study objectives, results and participants. Results: ‘FS-ICU-24’ is a good instrument to assess family satisfaction in the ICU. Family satisfaction levels are high (above 70%). In open-ended questions relatives refer less positive aspects such as the physical environment and communication. Some improvement suggestions are the possibility to increase privacy at waiting rooms and provide communication skills training to the staff. Conclusion: the integrative review shows that the FS-ICU-24 allows family satisfaction assessment and identification of improvements points in ICU.